(untitled) (Annals of Medical Research, 2025)
Waldenström macroglobulinemia (WM) is a lymphoproliferative disorder characterized by lymphoplasmacytic infiltration and Immunoglobulin M (IgM) monoclonal gammopathy. Bing-Neel syndrome (BNS), a rare complication of WM, arises from direct infiltration of malignant lymphoplasmacytic cells into the central nervous system (CNS). This report presents a 66-year-old female patient who developed BNS 15 years after the initial diagnosis of WM. The patient presented with neurological symptoms including dizziness, imbalance, memory impairment, and speech disturbances. Brain magnetic resonance imaging (MRI) revealed leptomeningeal and dural enhancement accompanied by vasogenic edema. Laboratory findings showed IgM lambda monoclonal gammopathy and lymphoplasmacytic infiltration. Although histopathological confirmation could not be obtained, the clinical and radiological findings supported the diagnosis of BNS. Following treatment with a combination chemotherapy regimen of rituximab and bendamustine (R-BENDA), along with high-dose methotrexate, clinical and radiological regression was observed. This case highlights that BNS may develop years after the initial diagnosis of WM and should be considered in the differential diagnosis.